Epigenetic Regulation of Resistance to Emotional Stress: Possible Involvement of 5-HT1A Receptor-Mediated Histone Acetylation - Minoru Tsuji; Kazuya Miyagawa; Hiroshi Takeda (Elsevier, 2014)
Abstract.: The ability to resist stress is an important defensive function of a living body. Thus, elucidation of the mechanisms by which the brain resists stress could help to pave the way for new therapeutic strategies for stress-related psychiatric disorders including depression. The present review focuses on the roles of brain 5-HT1A receptor-mediated epigenetic mechanisms in the development of resistance to emotional stress. Behavioral pharmacological studies have demonstrated that treatment with a 5-HT1A receptor agonist 24 h before testing suppressed the decrease in emotional behaviors induced by acute restraint stress. Studies with DNA microarray technology have revealed that histone deacetylase genes were decreased in the hippocampus of mice that had been pretreated with a 5-HT1A receptor agonist 24 h beforehand. This preliminary finding was supported by data that hippocampal acetylated histone H3 was increased in mice that had developed emotional resistance to acute restraint stress by 5-HT1A receptor agonist. Furthermore, the histone deacetylase inhibitor trichostatin A also protected against the emotional changes induced by acute restraint stress, accompanied by the induction of histone H3 acetylation. These findings suggest that epigenetic mechanisms that are functionally coupled with 5-HT1A receptors may play a key role in the development of resistance to emotional stress. Keywords:: 5-HT1A receptor, emotional stress resistance, epigenetic, histone acetylation